2003
DOI: 10.1007/s00125-003-1203-8
|View full text |Cite
|
Sign up to set email alerts
|

Type VIII adenylyl cyclase in rat beta cells: coincidence signal detector/generator for glucose and GLP-1

Abstract: Aims/hypothesis. The secretory function of pancreatic beta cells is synergistically stimulated by two signalling pathways which mediate the effects of nutrients and hormones such as glucagon-like peptide 1 (GLP-1), glucose-dependent insulinotropic peptide (GIP) or glucagon. These hormones are known to activate adenylyl cyclase in beta cells. We examined the type of adenylyl cyclase that is associated with this synergistic interaction. Methods. Insulin release, cAMP production, adenylyl cyclase activity, mRNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
110
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(123 citation statements)
references
References 73 publications
8
110
1
4
Order By: Relevance
“…Type VIII AC is synergistically activated by both G s α and calcium/ calmodulin (Cali et al, 1994) and thus acts as a coincidence detector for glucose and GLP-1 in the β cell. Elevation of glucose concentration (from 1.4 mM to 20 mM) alone did not increase cAMP accumulation in isolated rat primary β cells during a 15 min static incubation (Delmeire et al, 2003). However, the addition of GLP-1 (10 nM) at either low (1.4 mM) or high (20 mM) glucose did and this effect was abrogated by the L-type calcium channel blocker verapamil.…”
Section: Stimulation Of Camp Productionmentioning
confidence: 81%
See 2 more Smart Citations
“…Type VIII AC is synergistically activated by both G s α and calcium/ calmodulin (Cali et al, 1994) and thus acts as a coincidence detector for glucose and GLP-1 in the β cell. Elevation of glucose concentration (from 1.4 mM to 20 mM) alone did not increase cAMP accumulation in isolated rat primary β cells during a 15 min static incubation (Delmeire et al, 2003). However, the addition of GLP-1 (10 nM) at either low (1.4 mM) or high (20 mM) glucose did and this effect was abrogated by the L-type calcium channel blocker verapamil.…”
Section: Stimulation Of Camp Productionmentioning
confidence: 81%
“…Leech and co-workers performed RT-PCR on extracts from whole rat and human islets showing that AC III, IV,V,VI and VII were present in rat islets and AC V and VI and were found in human islets . A more recent RT-PCR analysis performed on α and β cells from the islets of Wistar rats clearly shows strong expression of transcripts for AC VI and VIII in β cells and AC II, III, IV, V and VI in α cells (Delmeire et al, 2003). Type VIII AC mRNA expression was also found in RINm5F and INS-1 clonal cell lines (Delmeire et al, 2003).…”
Section: Stimulation Of Camp Productionmentioning
confidence: 91%
See 1 more Smart Citation
“…From the observation that purified β-cells, lacking influence from the glucagon-producing α-cells, show reduced cAMP content and impaired secretory capacity, it was suggested that cAMP has a permissive role in glucose-induced insulin release and that the effect of the sugar on cAMP content represents amplification of glucagon-induced cAMP production (Schuit and Pipeleers, 1985). Among several adenylyl cyclases expressed in islet cells and insulin-secreting cell lines (Leech et al, 1999;Guenifi et al, 2000;Delmeire et al, 2003), the Ca 2+ -sensitive AC8 isoform has been proposed to integrate the cAMP responses to glucose and hormone receptor stimuli (Delmeire et al, 2003).…”
Section: Cyclic Ampmentioning
confidence: 99%
“…This was interpreted as Ca 2+ -dependent activation of the PDE1 family of phosphodiesterases (Landa et al, 2005). Islets and insulinsecreting cells express both Ca 2+ -regulated phosphodiesterases (Pyne and Furman, 2003;Landa et al, 2005) and adenylyl cyclases (Leech et al, 1999;Guenifi et al, 2000;Delmeire et al, 2003), and among the cyclases certain isoforms are stimulated, whereas others are suppressed by Ca 2+ (Willoughby and Cooper, 2007). It is therefore likely that the phase relationship between cAMP and Ca 2+ signals varies depending on the relative expression levels of different adenylyl cyclases and phosphodiesterases as well as on the type of stimulus (Fridlyand et al, 2007).…”
Section: Cyclic Ampmentioning
confidence: 99%